Green Life Style Sebagai Mediator Ecoliteracy dan Green Product Knowledge Terhadap Keputusan Pembelian Konsumen di Kota Ambon - Saul Ronald Jacob Saleky; Wendy Souisa (LPPM ITK, 2017)
To meet the needs and desires, consumers make decisions on the purchase of certain products. In making decisions, consumers are affected and consider many factors. This study aims to examine and analyze the effect of ecoliteracy and green product knowledge to the green lifestyle and purchasing decisions, either directly or indirectly. These results indicate that all independent variables have an effect on the dependent variable. Eco-literacy and green product knowledge have a direct influence on the green lifestyle and purchasing decisions. Furthermore, green lifestyle has a direct influence on consumer purchasing decisions in Ambon City. Similarly eco-literacy and green product knowledge has no direct influence on purchasing decisions through a green lifestyle. These results indicate that the directly effect of eco-literacy and green product knowledge was greater than the indirectly effect of through a green lifestyle. This means that the consumer's decision to buy a green product is more influenced by eco-literacy and green product knowledge than green lifestyle. Therefore, in order to encourage consumers more broadly to make purchases of green product, it would be better and easier for marketers and or manufacturers to enhance the eco-literacy and green product knowledge of the consumer.